Research on Enterprise Management Innovation in the Context of Digital Transformation - Xiao, Mengyao (Asia Pacific Economic and Management Review, 2025)
Under the booming environment of the digital economy, enterprises are ushering in unprecedented development opportunities, but also facing many challenges. This paper examines the impact of technological innovation on the management model, and discusses how technologies such as big data, artificial intelligence and blockchain can contribute to the digital transformation of enterprise management. The study finds that by optimising resource allocation, improving decision-making and improving customer experience through technological innovation, companies can achieve significant improvements in operational efficiency and move towards sustainable development.